A naphthodithieno[3, 2-b]thiophene-based copolymer as a novel third component in ternary polymer solar cells with a simultaneously enhanced open circuit voltage, short circuit current and fill factor. (9th March 2018) - Sun, Yuqian; Guo, Biao; Chen, Youchun; Zhang, Weifeng; Li, Xiang; Yu, Gui; Li, Fenghong
Abstract : Ternary polymer solar cells with simultaneously improved V OC, J SC and FF have been achieved by doping PV12 as a third component. Abstract : A dialkoxyl-substituted naphthodithieno[3, 2- b ]thiophene-based copolymer (PV12) was applied as a third component for ternary polymer solar cells (PSCs) based on PCDTBT1− x :PV12 x :PC71 BM. In Al-only ternary PSCs with x = 0.15, a power conversion efficiency (PCE) of 6.73% was achieved due to simultaneous enhancement in the open circuit voltage, short circuit current and fill factor, which is much higher than the PCE of 5.28% for Al-only binary PSCs based on PCDTBT:PC71 BM and 2.93% for Al-only binary PSCs based on PV12:PC71 BM. The PCE reached 7.69% when IIDTh-NSB as a cathode interlayer was introduced between the ternary active layer and Al. Ultraviolet photoemission spectroscopy measurements demonstrated a cascade-type energy level alignment at the ternary PCDTBT(D1)/PV12(D2)/PC71 BM(A) junction. As a result, the voltage limitation was overcome at the D1/D2/A junction. Ultraviolet-visible absorption and external quantum efficiency spectra showed that PV12 had complementary absorption to PCDTBT in the solar spectrum. Atomic force microscopy and transmission electron microscopy images showed that the morphology and phase separation of the active layer were optimized by adding PV12. Photoluminescence spectral investigations suggested that the Förster resonance energy transfer from PCDTBT to PV12 occurred in the ternary PSCs under illumination. Finally, the PCEs of the ternary PSCs are not as sensitive to the thickness of the active layer as those of the binary PSCs, which is important for the roll-to-roll coating processing of organic photovoltaic modules.